Deviant Versus Nondeviant Routines, Social Guardianship and Adolescent Victimization in the Rural Context of China - Cheung, Nicole W. T. (Journal of interpersonal violence, 2022)
There is limited knowledge on the possible pathways of victimization among rural dwellers during adolescence in developing contexts, such as rural China, where victimization may compound developmental disadvantages of rural adolescents. Guided by the lifestyle/routine activity theory, the goal of this study thus was to examine how far delinquent lifestyles (delinquent involvement and delinquent peer association); nondeviant routine activities (unstructured socializing with peers, structured activities, and solitary activities); and social guardianship within family, school, and neighborhood contribute to juvenile victimization in a rural setting. The outcomes of interest covered direct victimization (violent, property, and sexual) and indirect victimization (witnessing community violence). The study included 2,839 adolescents (51.2% male; mean age = 13.88 ± 0.90 years) from 30 middle schools in rural China. The delinquent peer influence as a risk factor of direct and indirect victimization appeared to be more profound than delinquent involvement. Solitary activities consistently put rural adolescents at greater risk of direct and indirect victimization, and their role was stronger than that of rural adolescents? delinquent involvement. No victimization outcomes were predicted by unstructured socializing with peers and structured activities. Attachment to family caregivers and neighborhood cohesion were the strongest social guardianship predictors across all forms of victimization. These results suggest that alongside social guardianship and delinquent lifestyles, rural isolation should be addressed in managing juvenile victimization. The insignificant role of unstructured socializing with peers may raise the need to clarify its conceptual relevance to rural settings. The implications for improving the underdeveloped preventive measures against victimization of rural adolescent populations in developing societies are described.